Comparison of Two Transvenous Temporary Pacemaker Fixation Methods: FIX-IT Trial - Galvão, Raoni de Castro; Papelbaum, Bruno; Neves, Raquel Almeida Lopes; Cezar, Fabricio Mantovani; Jesus, Luciene Dias de; Padilha, Jaqueline Correia; Duarte, Carlos Eduardo; Vasconcelos, Jose Tarcísio Medeiros de; Galvão-Filho, Silas dos Santos (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
Introduction: the necessity for a temporary pacemaker (TP) goes through several scenarios. Some patients require the device to complete an infection treatment, regain the pace after myocardial infarction, or while awaiting the release of the definitive device by the health care provider. Regardless of the TP passage technique, good electrode fixation is essential, avoiding dislocation and the necessity for repositioning, among other complications. Objective: to compare two forms of TP fixation, one under direct fixation to the skin and the other keeping the venous introducer connected to the plastic protection through the pacemaker electrode lead. Methods: Forty patients were randomized, 20 in each group. Data regarding the procedure time, electrode lead position, command thresholds, sensitivity, and complications were recorded. The primary outcome considered was the necessity for repositioning or exchange of transvenous TP and secondary any complication without the necessity to reposition it. Results: There were no significant differences in the total duration of the procedure between the groups in the initial position of the electrode and the access route used. The group with plastic protection had a higher primary outcome (60%) than the direct fixation group (20%; p = 0.0098). There were no differences regarding the secondary outcome (p = 1.0). The group with plastic protection also had more total complications compared to the other group (p = 0.0262). Conclusion: Direct fixation of the pacemaker electrode lead was safer concerning the fixation with plastic protection, reducing complications such as electrode dislocation requiring repositioning or replacement without increasing the procedure time.